Effects of different quantites of silk and cotton waste used as fibre reinforced composites with, recycled PA, and PC, PPHDPE on resultant composites structure - (:unkn) unknown (UNIV ZAGREB, FAC FORESTRY, 2002)
In recent years fibre reinforced composite structures are widely used in engineering. Fibres such as silk and cotton fibres used in many areas of textiles. But their use as a fibre reinforced composite structure is quite a new one (especially in the form of waste). Using waste fibres in a composite structure very important in terms of economic, environmental and technological advances. In this work various length of (1mm to 5mm) waste silk and waste cotton fibres were added to HDPE and PP polymer in the mixing, quantities of (Polymer/Fibre) % 100/%, %97/ %3, %94 / %6 to produce a composite structure. On the other hand known lengths of (1mm, 2.5mm and 5mm) waste silk and waste cotton fibres were added to recycled PA6 and PC polymers in the mixing quantities of % 100 / % 0 and % 97 / %3, twin screw extruder was employed for production of composites. All samples were tested in terms of mechanical, elasticity modulus, yield strength, tensile strength, elongation, Izod impact strength and hardness MFI the results were tabulated and discussed. Results have shown that cotton and silk fibres behaves different in the composite structure. Waste silk fibre composites gives better mechanical properties than waste cotton fibre.
Keywords: silk; cotton; HDPE; PP; recycled PA6; recycled PC; composite materials; polymer composite; COMMON THERMOPLASTICS; MECHANICAL-PROPERTIES; CELLULOSIC FILLERS; PROCESSING AIDS; COUPLING AGENTS; FIBERS; METHACRYLAMIDE; EFFICIENCY